Multi-fractal DFA analysis of masseter muscles SEMG signal in patients with TMD, pilot study. (July 2021) - García-Espinosa, Luis A.; Minor-Martínez, Arturo; Pérez-Escamirosa, Fernando; Morales-González, Julio; Rodríguez-Castañeda, Ivonne; Flores-Ramírez, Bernardo; Pacheco-Guerrero, Nicolas; Ángeles-Medina, Fernando
Highlights: Multifractal DFA outperforms traditional RMS and MNF methods on SEMG assessment. DFA-based SEMG analysis is less sensitive to factors affecting SEMG's reproducibility. DFA-based SEMG analysis allows evaluating masseter muscles' neuromuscular asymmetry. A force sensor is not necessary for DFA-based SEMG analysis of masseter muscles. DFA-based SEMG analysis could improve dental treatments evaluation. Abstract: Objective: The objective of this work is to present a new application of the multi-fractal detrended fluctuation analysis (DFA) for the analysis of bilateral surface electromyography (SEMG) signal of masseter muscles as an aid in the diagnosis and follow-up of patients with temporomandibular disorder (TMD). Methods: Ten adult patients with TMD rehabilitated by physiological occlusal splint therapy participated in the study. We obtained bilateral SEMG of masseter muscles during two different isometric contractions: 1) centric occlusal (CO) position and 2) no posterior dental contacts (NPDC) position. Neuromuscular asymmetry index was calculated based on time-dependent variables RMS, MNF, and optimal self-similarity exponent at two times of the study, the beginning and the end of treatment. Results: The neuromuscular asymmetry index calculated based on the optimal self-similarity exponent decreases significantly (p = 0.002) while the patients show symptomatological and functional improvement assessed by physical and clinical evaluation at the end of the treatment. On the other hand, the asymmetry indices calculated based on RMS or MNF showed significance values of p = 0.571 and p = 0.241, respectively, despite the patients' symptomatological and functional improvement. Conclusion: The proposed analysis offers greater precision in the SEMG analysis of patients' masseter muscles with TMD than traditional methods. This precision suggests that DFA is less sensitive to distance variation between electrodes, muscular enervation zone variation, and other factors affecting traditional RMS and MNF methods' reproducibility. In future work, we will increase the number of study subjects and evaluate multi-fractal DFA's reproducibility.